The Implementation of Qur’anic Reading and Writing Learning to Improve Students' Qur'anic Reading Skills at SMK Muhammadiyah 2 Klaten - Aji Satrio Kuncoro; Chusniatun Chusniatun (SAINTIS Publishing, 2025)
The purpose of learning to read and write the Qur'an (BTQ) is to teach students how to understand the texts of the Qur'an, including the ability to write, read, and connect verses. This study aims to evaluate the implementation of learning to read and write the Qur'an (BTQ) in improving students' Qur'an reading skills at SMK Muhammadiyah 2 Klaten. This study uses a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that learning to read and write the Qur'an can improve students' Qur'an reading skills, especially through the Iqra' and Anak Surga (AGA) methods. However, there are several inhibiting factors such as variations in student ability levels, motivation, and teacher teaching quality that hinder the success of the Qur'an reading and writing program. Therefore, a more varied teaching method is needed and adjusted to students' needs to improve overall learning outcomes.